"Living in contact with nature". The emergence of socio-environmental conflicts around urban-real estate extractivism - Astelarra, Sofía (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Within the framework of the “Jornadas Fundamentos y Aplicaciones de la Interdisciplina” (JFAI) and the roundtable "Nature, socio-territorial conflicts and socio-environmental issues" we will address the following questions: What disputes arise in the context of social struggles for the appropriation, management and use of nature? How does the deepening of the extractivist model affect the different social actors, such as native peoples, fumigated peoples, peasant movements, local/regional organizations and/or assemblies, among others?To do so, I will take as a starting point the phrase "living in contact with nature" and I will focus on the emergence of socio-environmental conflicts around urban-real estate extractivism, since these narratives are deployed by the social actors involved. The key of analysis from which to read these conflicts is the field of American political ecology and with contributions from critical geography and sociology. For the understanding and analysis of socio-environmental conflicts I use the methodology proposed by Merlinsky (2013), for which I make a historical journey that begins in the mid-1990s, when the first controversies are recorded in the public spheres in the Partido de Tigre; from the systematization the emblematic cases with their dynamics and main milestones have been determined